Pseudo magic cubes: A multidimensional data hiding scheme exploiting modification directions for large payloads. (January 2021) - Ranjani, J. Jennifer; Zaid, Fauzan
Abstract: In this paper, a multidimensional data hiding scheme exploiting modification directions (EMD) that can embed high payload information without causing much distortion, is proposed. Traditional, EMD embeds a secret digit represented in the ( 2 n + 1 ) − ary system has a maximum 1.161 bpp payload. In the proposed work, a secret-digit represented in the n 3 − ary notational system is hidden, on a group of 3 pixels that are chosen based on a random sequence yields a payload of l o g 2 ( n ) . Hence, an increase in the dimension, n − of the neighborhood set results in the increased payload. We have conducted extensive experiments on the standard image set to verify the embedding efficiency and visual quality of the stego image. The PSNR of the proposed algorithm for embedding 2.3219 bpp in a cover image of 512 × 512 is 45.13 dB, which implies that the visual quality of the stego image has not degraded even for large payloads. We have also verified that the proposed technique is undetectable during steganalysis. Graphical abstract: Highlights: A multi-dimensional neighborhood set, using Magic Cubes is proposed, for data hiding. Pseudo magic cubes of same order are generated by transforming along the rolling axis. Proposed method demonstrates high embedding capacity with minimal distortion. Multi-dimensional neighborhood set is responsible for increasing the embedding capacity. The multi-dimensional neighborhood set is independent of the number of cover pixels.